FCS in STED microscopy: studying the nanoscale of lipid membrane dynamics. - Mueller, V; Honigmann, A; Ringemann, C; Medda, R; Schwarzmann, G; Eggeling, C (2013)
Details of molecular membrane dynamics in living cells such as lipid-protein interactions or the incorporation of molecules into lipid "rafts" are often hidden to the observer because of the limited spatial resolution of conventional far-field optical microscopy. Fortunately, the superior spatial resolution of far-field stimulated-emission-depletion (STED) nanoscopy allows gaining new insights. Applying fluorescence correlation spectroscopy (FCS) in focal spots continuously tuned down to 30 nm in diameter distinguishes free from anomalous molecular diffusion due to transient binding, as for the diffusion of fluorescent phosphoglycero- and sphingolipid analogs in the plasma membrane of living cells. STED-FCS data recorded at different environmental conditions and on different lipid analogs reveal molecular details of the observed nanoscale trapping. Dependencies on the molecular structure of the lipids point to the distinct connectivity of the various lipids to initiate or assist cellular signaling events, but also outline strong differences to the characteristics of liquid-ordered and disordered phase separation in model membranes. STED-FCS is a highly sensitive and exceptional tool to study the membrane organization by introducing a new class of nanoscale biomolecular studies.